A Rare Case of Metachromatic Leukodystrophy (MLD): Case of Metachromatic Leukodystrophy - Naveed, Aiman; Ahmad, Ikhlaq; Khan, Bilal; Khan, Saeed; Mughal, Hamdah Bashir; Quddus, Abdul (Pakistan Journal of Health Sciences, 2025)
Metachromatic Leukodystrophy (MLD) is a rare hereditary lysosomal storage disorder affecting white matter, often leading to progressive motor and cognitive decline. This case presents a 30-month-old child from a consanguineous family who was in good health four months prior but initially exhibited mild symptoms of diarrhea and a chest infection before rapidly deteriorating neurologically. The delayed diagnosis highlights the challenges of early recognition in resource-limited settings. MRI findings, coupled with genetic testing, confirmed the diagnosis, emphasizing the importance of integrating neuroimaging with molecular diagnostics. This case underscores the critical need for prenatal and newborn genetic screening, particularly in populations with a high prevalence of consanguinity, to facilitate timely interventions and improve disease management. Early recognition and a multidisciplinary approach, including genetic counseling, can enhance outcomes and inform future preventive strategies for at-risk families.